Consumers’ behavioural intention to use E-Wallet during the Pandemic of Covid-19: applying the unified theory of acceptance and use of Technology - Sharinah Puasa; Tan, JiaLe; Haneffa Muchlis Gazali; Nurjeehan Ayub (Penerbit UMS, 2021)
The new norm of living during the COVID-19 pandemic has changed the way consumers perceived e-wallet. This study aims to: (i) examine consumers’ behavioural intention level to use e-wallet during the COVID-19 pandemic; and (ii) applied the Unified Theory of Acceptance and Use of Technology (UTAUT) in investigating the factors influencing the behavioural intention to use e-wallet during the pandemic situation. A survey questionnaire was conducted through an online platform with consumers in Kuala Lumpur. The descriptive finding (n = 205) indicates a moderate to high level of consumers’ behavioural intention to use e-wallet during the pandemic. Statistical analysis found that Performance Expectancy (p < 1%), Effort Expectancy (p < 1%) and Facilitating Conditions (p < 10%) have significant positive relationships with consumers’ behavioural intention to use e-wallet during the pandemic. The results highlight the critical factors of behavioural intention to use e-wallet in which the Performance Expectancy, Effort Expectancy and Facilitating Conditions remain significant during the pandemic situation. Remarkably, the consumers' behavioural intention to use e-wallet is strongly influenced by Performance Expectancy compared to other variables. On the other hand, Social Influence is found insignificant in influencing the consumers’ behavioural intention to use e-wallet during the pandemic.